Removal of Deeply Impacted Mandibular Molars by Sagittal Split Osteotomy - Erol Cansiz; Sabri Cemil Isler; B. Alper Gultekin (Hindawi Limited, 2016)
Mandibular third molars are the most common impacted teeth. Mandibular first and second molars do not share the same frequency of occurrence. In rare cases the occlusal surfaces of impacted molars are united by the same follicular space and the roots pointing in opposite direction; these are called kissing molars. In some cases, a supernumerary fourth molar can be seen as unerupted and, in this case, such a supernumerary, deeply impacted fourth molar is seen neighboring kissing molars. The extraction of deeply impacted wisdom molars from the mandible may necessitate excessive bone removal and it causes complications such as damage to the inferior alveolar nerve and iatrogenic fractures of the mandible. This case report describes the use of the sagittal split osteotomy technique to avoid extensive bone removal and protect the inferior alveolar nerve during surgical extruction of multiple impacted teeth.